A system developer's perspective of managing cirm implementation in local governments: lessons from Malaysia - Nasirin, S. (2012)
This paper proposes a system developer?s perspective of the Citizen Relationship Management (CiRM) system implementation framework in the Malaysian local governments. The framework was developed based upon two in-depth cross-case studies which were conducted in two leading local governments in Malaysia. In addition to confirming the familiar determinants found in the literature, the paper also suggests the significance of "publicity" as a factor which should not be overlooked when CiRM implementation initiative is considered.